Biomechanical considerations of semi-anatomic glass fiber-reinforced (GFRC) composite implant for mandibular segmental defects : A technical note - Väisänen, Antti (My University, 2024)
Objectives: The aim of this study was to investigate the selected biomechanical properties of semi-anatomic implant plate made of biostable glass fiber-reinforced composite (GFRC) for mandibular reconstruction. Two versions of GFRC plates were tested in in vitro loading conditions of a mandible segmental defect model, for determining the level of mechanical stress at the location of fixation screws, and in the body of the plate. Methods: GFRC of bidirectional S3-glass fiber weaves with dimethacrylate resin matrix were used to fabricate semi-anatomic reconstruction plates of two GFRC laminate thicknesses. Lateral surface of the plate followed the contour of the resected part of the bone, and the medial surface was concave allowing for placement of a microvascular bone flap in the next stages of the research. Plates were fixed with screws to a plastic model of the mandible with a large segmental defect in the premolar-molar region. The mandible-plate system was loaded from incisal and molar locations with loads of 10, 50, and 100 N and stress (microstrain, με) at the location of fixation screws and the body of the plate was measured by strain gauges. In total the test set-up had four areas for measuring the stress of the plate. Results: No signs of fractures or buckling failures of the plates were found during loading. Strain values at the region of the fixation screws were higher with thick plate, whereas thin plates demonstrated higher strain at the body of the plate. Vertical displacement of the mandible-plate system was proportional to the loading force and was higher with incisal than molar loading locations but no difference was found between thin and thick plates. Conclusion: GFRC plates withstood the loading conditions up to 100 N even when loaded incisally. Thick plates concentrated the stress to the ramus mandibulae region of the fixation screws whereas the thin plates showed stress concentration in the angulus mandibulae region of the fixation and the plate itself. In general, thin plates caused a lower magnitude of stress to the fixation screw areas than thick plates, suggesting absorption of the loading energy to the body of the plate.
Keywords: Mandibular reconstruction, implant, fixation plate, free flap, fiber-reinforced composite, FRC